Improving the Mechanical Properties of Mortars by Adding Metal-Doped Zinc Oxide Nanoparticles - Max Lima; Ítalo M. Gonçalves; Goreti Pereira; Giovannia A. L. Pereira (Engineering Proceedings, 2023)
The evolution of construction engineering depends on the development of cementitious materials with optimized properties and lower environmental impacts, such as the preparation of mortars with higher mechanical resistance and durability. Nanotechnology is a promising tool for industrial innovation, enhancing material properties like durability and mechanical performance. Thus, herein, we prepared mortars incorporating ZnO nanoparticles and evaluated their properties. The results showed that smaller percentages of ZnO presented better performance in consistency tests, and all samples containing ZnO showed higher mechanical resistance than the reference, thus suggesting the great potential of nanoparticles in optimizing the mechanical properties of mortars.